PENGEMBANGAN MEDIA AUDIO-VISUAL PADA SUBTEMA MANUSIA DAN LINGKUNGAN UNTUK MENINGKATKAN KETERAMPILAN MENYIMAK SISWA KELAS V SEKOLAH DASAR - Yuniarti, Ika; Masyhud, M. Sulthon; Rahayu, Ucu (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
The problem in class V of SDN Tanggungan is the low listening skills of the participants or only twelve students (48%) are complete. This study aims to describe the development of appropriate Audio-Visual Media (valid, practical, and effective) on the subtheme of Humans and the Environment to improve the skills of listening to factual problems of grade V elementary school students. The type of research is research and development (R&D) with the Borg & Gall development model. The subject of the study was grade V students of SDN Tanggungan which totaled thirty. The instruments used were validation sheets, observation sheets, questionnaire sheets, and listening skill test sheets. Data analysis refers to the criteria of validity, practicality and effectiveness. Based on the results of the research and discussion, the following were obtained: (1) The results of the validation of Audio-Visual Media experts obtained a score of 88.75% and were within the criteria of being very valid; (2) The results of observation of the implementation of learning and the questionnaire of students' responses to Audio-Visual Media obtained scores of 89.5% and 97.36% respectively and were in the good and very good criteria; and (3) The results of the pretest and posttest scores after the implementation of learning using Audio-Visual Media obtained  a significance value (2-tailed) of 0.00 < 0.05, so that there was a difference in students' listening skills between the experimental and control classes.